2019
DOI: 10.1111/crj.13014
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive saliva swallowing test and water swallowing test may identify a COPD phenotype at high risk of exacerbation

Abstract: Introduction Patients with chronic obstructive pulmonary disease (COPD) are known to present with dysphagia from an early stage. Dysphagia leads to swallowing‐related complications, in turn leading to COPD exacerbation. Dysphagia screening is recommended; however little is known of its utility in detecting a COPD phenotype at risk for exacerbation. The simple swallowing provocation test (SSPT), considered to be a standard screening test, requires specific equipment, physician skill and patient discomfort. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…As shown in our previous study, the optimal cutoff value of swallow screening tests is different in stable COPD patients (in whom the swallowing disorder is often subclinical) than in more apparent swallowing disorders associated with stroke or neurological conditions. 4 , 5 ) Therefore, the significant differences shown in Fig. 2 may be of importance even if the results were unchanged with respect to the commonly applied thresholds (as in Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in our previous study, the optimal cutoff value of swallow screening tests is different in stable COPD patients (in whom the swallowing disorder is often subclinical) than in more apparent swallowing disorders associated with stroke or neurological conditions. 4 , 5 ) Therefore, the significant differences shown in Fig. 2 may be of importance even if the results were unchanged with respect to the commonly applied thresholds (as in Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that a low RSST has a high impact on the risk of future exacerbation. 4 , 5 ) The long-term effects of IFC-TESS and improvements in RSST will be determined in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An assessment of swallowing function revealed no paralysis of the tongue or face. In the repetitive saliva swallowing test (RSST: normal is more than 3 times per 30 s), [7] he swallowed six times in 30 s. However, he had wet hoarseness in 3 mL of thick water-swallowing test. Therefore, only indirect therapy (without food) was performed.…”
Section: Casementioning
confidence: 99%